Designing, synthesis and bioactivities of 4-[3-(4-hydroxyphenyl)-5-aryl-4, 5-dihydro-pyrazol-1-yl]benzenesulfonamides. (1st January 2017) - Gul, Halise Inci; Mete, Ebru; Eren, Sakip Emre; Sakagami, Hiroshi; Yamali, Cem; Supuran, Claudiu T.
Abstract: In this study, 4-[3-(4-hydroxyphenyl)-5-aryl-4, 5-dihydro-pyrazol-1-yl]benzenesulfonamide (1 –9 ) types compounds were synthesized and their chemical structures were confirmed by 1 H NMR, 13 C NMR and HRMS spectra. Cytotoxic and carbonic anhydrase (CA) inhibitory effects of the compounds were investigated. Cytotoxicity experiments pointed out that compound4, (4-[5-(4-chlorophenyl)-3-(4-hydroxyphenyl)-4, 5-dihydro-pyrazol-1-yl]benzenesulfonamide), exerting the highest tumor selectivity (TS) and potency selectivity expression (PSE) values, can be considered as a lead compound of this study in terms of development of novel anticancer agents. All synthesized sulfonamides showed a good inhibition profile on hCA IX and XII in the range of 53.5–923 nM and 6.2–95 nM, respectively. These compounds were 2.5–13.4 times more selective for the inhibition of hCA XII versus hCA IX, except compound2 which had similar inhibitory action towards both isoenzymes.